SAP project system handbook - Dowling, Kieron N. (McGraw Hill, 2008)
Centralize and Control Enterprise Project Management Plan, execute, and track projects across the entire lifecycle using SAP Project System (PS) and the in-depth information contained in this comprehensive volume. SAP Project System Handbook explains how to configure PS for optimal performance, design structures and networks, create project blueprints, generate cost estimates and materials demands, and use the latest SAP tools. You will find full details on scheduling work, automating and tracking billing and POs, triggering events, and integrating with most other SAP modules. An invaluable.